2006
DOI: 10.1016/j.amjhyper.2006.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Prehypertension and Obesity in AdolescentsA Population Study

Abstract: Prehypertension is very common among Israeli adolescents. A substantial number of adolescents exhibit a BMI greater than normal. As both of these factors are known to be asssociated with increased cardiovascular risk, early institution of healthful lifestyle changes in a large proportion of this age group is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 19 publications
6
25
0
Order By: Relevance
“…Ag e -An d S e x -s p e c i f i c P r e v a l e n c e o f No r ma l , Ov e rwe i g h t , a n d Ob e s i t y i n Ch i n a Ru r a l Ad u l t s T a b l e 3 . P r e v a l e n c e o f P r e h y p e r t e n s i o n a n d (18,19). In our study, the prevalence of overweight and obesity was higher in females than in males.…”
Section: Study Subjectsmentioning
confidence: 46%
“…Ag e -An d S e x -s p e c i f i c P r e v a l e n c e o f No r ma l , Ov e rwe i g h t , a n d Ob e s i t y i n Ch i n a Ru r a l Ad u l t s T a b l e 3 . P r e v a l e n c e o f P r e h y p e r t e n s i o n a n d (18,19). In our study, the prevalence of overweight and obesity was higher in females than in males.…”
Section: Study Subjectsmentioning
confidence: 46%
“…The prevalence of prehypertension ranges between 31.2 − 33% in different countries 11,12) . An Israeli study indicated that the prevalence of prehypertension was 23.2% in adults 13) , and would increase up to 56.8% in men and 35.8% in women within 3 years 14) . It has been reported that prehypertension is frequently associated with other CVD risk factors 12) , a higher risk of developing myocardial infarction or coronary artery diseases 15,16) , and higher probabilities of hospitalization and mortality 17) .…”
Section: Introductionmentioning
confidence: 99%
“…However, at the present time there is clearly a need for health services to adapt to the increased demands from health-care problems among youths. Obesity in adolescence tracks into adulthood (2,31) and is associated with increased incidence of type 2 diabetes mellitus in youth (10,26,32) . It is important to document the burden of adolescent obesity and identify risk factors which are amenable to intervention.…”
mentioning
confidence: 99%